Environmental features around roost sites drive species-specific roost preferences for boreal bats - Kati M. Suominen; Eero J. Vesterinen; Ilkka Kivistö; Maria Reiman; Tarmo Virtanen; Melissa B. Meierhofer; Ville Vasko; Tarja Sironen; Thomas M. Lilley (Global Ecology and Conservation, 2023)
Bats and their reproductive roost sites are strictly protected by legislation in Europe. Although knowledge on foraging habitats of boreal bats has increased vastly over the last decades, little is known on how habitat surrounding the roosts influences the selection of roost sites. We combined citizen science and molecular methods to determine the most critical environmental features within different radiuses around roost sites of bats inhabiting human settlements at the northernmost edge of their distribution range in Finland. We compared six different land-use types around the roost sites to randomly selected points for each species to determine at which radiuses around the roost are land-use types most critical. We found that for the northern bat (Eptesicus nilssonii), built environment, open areas, and water within the 200 m radius were the most important in roost site selection. The Brandt’s myotis (Myotis brandtii) favored roost sites in landscape not affected by human disturbance within 5 km radius. Based on our results, the surrounding habitat around a roost plays a vital role for bat species, and it should be protected along with the roost and considered in land-use planning. Furthermore, species-specific variation in roost site selection should be considered in conservation planning.